Efeito de diferentes sistemas de polimento na rugosidade e resistência flexural de cerâmicas odontológicas - NEVES, Debora de Paula (2022)
The aim of this study was to evaluate the action of different types of polishing on the surface roughness and flexural strength of ceramics. Scanning electron microscopy (SEM) and energy dispersive x-ray spectrometry (EDS) were performed on the abrasive tips before and after polishing. 200 discs were made (100 zirconia lithium silicate (ZLS) / 100 feldspar vitreous ceramic) of which ten of each material did not receive any surface alteration (C - positive control). The others were roughened with a FF diamond bur and divided into groups (n = 10) according to surface treatment: FF - roughened (Negative control); GL - Glaze; DH - Pk5 Dhpro, OP - Optrafine; SH - Ceramisté; DU - Durapol; EC - Cerapol; SO - Sof-Lex; SUP - Supply; and subjected to the surface roughness test and biaxial bending test. Data were submitted to two-way ANOVA, Tukey, Dunnett and Pearson's correlation tests (α = 0.05). There was a statistical difference between the polishing factors and ceramic type, as well as for the interaction of the factors (p < 0.01) both in the roughness and strength parameters. For Feldspathic roughness, only SH and SO showed no significant difference in relation to C. A higher roughness was observed in the ZLS polishes, except for the GL group that promoted greater smoothness and resistance than the other kits. In Feldspathica, there was no significant difference in resistance between the systems. It was concluded that: 1) the effectiveness of the polishing protocol is influenced by the ceramic, with Feldspathic polishing and ZLS glaze being better; 2) the Sof-Lex and Ceramisté polishing kits provided less roughness in the Feldspatic ceramic; 3) the application of glaze is essential in ZLS to obtain greater smoothness and strength in this ceramic; 4) there is no correlation between flexural strength and surface roughness for the evaluated ceramics